Specific features of occupational pathology in the Murmansk region in 2007-2021 - Syurin S.A.; Kizeev A.N.; Polyakova E.M. (Российская Арктика)
Introduction. Employees of enterprises in the Murmansk region are exposed to harmful production factors that increase the risk of developing occupational diseases.